Fundamental Concepts in Max Weber’s Sociology of Religion - Adair-Toteff, Christopher. author. aut Link
IX, 206 p.
Keywords: This book helps explain some of Max Weber's key concepts such as charisma, asceticism, mysticism, pariah-people, prophets, salvation, and theodicy and places them within the context of Weber's sociology of religion.